FAKTOR-FAKTOR YANG MEMPENGARUHI KEMISKINAN RUMAH TANGGA DI KOTA KENDARI TAHUN 2014 - Wulandari, Nike Roso (Pascasarjana Universitas Halu Oleo, 2016)
The aims of this study were; (1) to determine the characteristics of household poverty in Kendari city (2) to determine factors that affect household poverty in Kendari city in 2014; (3) to determine the poverty tendency based on factors that affect poverty in Kendari city. Data were analyzed of using descriptive analysis, chi squared analysis and inferential analysis of Logistic Regression. Data were obtained from the result of Susenas 2014 which were collected by the Central Agency for Statistics of Kendari city. Results of the study were: (1) The characteristics of Household poverty are migrants, male, aged under 60 years, the number of family members is more than 4 people, the level of education is less than high school, and work in the formal and informal sector. (2) a partial examination using The Chi Square analysis showed that all the variables under investigation including migration status, household head’s gender, household head’s age, number of family members, household head’s level of education, employment status of the household head , had significant effect on household poverty, given that the p value = 0.000,which was below α = 0.05. Simultaneous examination using the logistic regression test showed that all variables under investigation had significant effects on the household poverty; (3) if seen from Odds Ratio, two variables, i.e., education and number of family members, exhibited a higher tendency than did other variables. Keywords: Factors affecting poverty, household, migration status, gender, age, number of family members, Educational level, Employment Status.